Investigation on harvested energy-assisted relay selection modes in wireless powered full-duplex relaying networks - Pham Thi My Linh; Nguyen Thai Anh; Do Dinh Thuan; Tran Thu Ha (Journal of Technical Education Science, 2017)
In this paper, the authors investigate relay selection for decode-and-forward (DF) Full-duplex (FD) based wireless energy harvesting relaying networks. Considering time-switching based relaying (TSR) protocol, this investigation is concerned with the performance of maximum harvested energy relay selection (MHE-RS) scheme. In particular, this work analyzes the system performance in terms of outage probability (OP) and throughput over Rayleigh fading channels. As important achievement, the integral-form for exact expression and closed-form for approximate expression are derived. Finally, these analytical expressions are validated by the Monte-Carlo simulation.